Zeuxapta seriolae (Meserve, 1938) Infections in Cultured Greater Amberjack, Seriola dumerili (Risso, 1810), from the Middle Eastern Adriatic Sea - Slavica Čolak; Tomislav Šarić; Matko Kolega; Danijel Mejdandžić; Relja Beck; Perla Tedesco; Marialetizia Fioravanti; Andrea Gustinelli; Monica Caffara (Fishes, 2026)
Parasitic diseases pose significant challenges to the success of mariculture. The health management strategies used in sea-cage aquaculture are not completely effective at preventing parasites from entering through interactions with wild fish. This study monitored the health status of greater amberjack (Seriola dumerili, Risso 1810) over a two-month period following their introduction to the farm in the Middle Eastern Adriatic Sea in July 2019. Zeuxapta seriolae was detected on the gills after 722 degree days (DD), with a 28% prevalence, a mean abundance of 1.00 parasite per fish (four examined arches), and a mean intensity of 3.57 parasites per infected fish. From 985 DD, prevalence was 100%; the parasite burden continued to rise, and by the final sampling at 1535 DD, the mean abundance reached 212.68 parasites per fish (53.17 per gill arch). At that point, fish express a sudden loss of appetite; no external symptoms were observed, except for mortality. This is the first report of Z. seriolae in cultured greater amberjack in the Adriatic Sea, and the study emphasises the difficulties in applying effective biosecurity measures in floating net cages.

International multicentre study to validate the Segmental Sedimentation and Counting Technique (SSCT) for the surveillance of Echinococcus multilocularis in red fox - Gérald Umhang; Fanny Bastien; Christophe Caillot; Gunita Deksne; Jacek Karamon; Rebecca Davidson; Maira Mateusa; Małgorzata Samorek-Pieróg; Azzurra Santoro; Federica Santolamazza; Relja Beck; James O’Shaughnessy; et al. (Veterinary Parasitology, 2026)

Bonamia exitiosa in European Flat Oyster (Ostrea edulis) on the Croatian Adriatic Coast from 2016 to 2020 - Dražen Oraić; Relja Beck; Željko Pavlinec; Ivana Giovanna Zupičić; Ljupka Maltar; Tihana Miškić; Žaklin Acinger-Rogić; Snježana Zrnčić (Journal of Marine Science and Engineering, 2021)
The annual production of European flat oysters (Ostrea edulis) in Croatia is about 50 to 65 tons, and it has a long tradition. All Croatian oyster farms are subjected to the national surveillance program aiming to detect the presence of Bonamia ostreae and Marteilia refringens according to the Council Directive 2006/88/EC. Within the surveillance program, the first findings of the parasite Bonamia spp. occurred in 2016 in two production areas in the north and south of the Eastern Adriatic coast. The repeated findings of the parasite were noted up to 2020 but also on two additional sites in the north. The parasite was detected by cytological analysis of stained heart smears, histological examination, and PCR. PCR positive samples were sequenced for SSU rDNA gene, and BLAST analysis confirmed infection with Bonamia exitiosa. Attempts to prove the Pacific oyster as a putative vector of the parasite failed. The infection prevalence from 2016 until 2020 ranged from 3.3 to 20% in different sites. No mortalities were reported from the infected sites, and it seemed that infection of flat oysters with B. exitiosa did not affect their health. The study has not shown the source and way of infection spread, which imposes the need for more comprehensive molecular and epidemiological studies.

The First Genetically Confirmed Case of Human Ophthalmomyasis Due to Oestrus ovis (Diptera Oestridae) in Bosnia and Herzegovina - Renato Pejic; Sanja Jakovac; Relja Beck (Acta Parasitologica, 2020)

Assessment of predominant bacteria in noble pen shell (Pinna nobilis) collected in the Eastern Adriatic Sea - Željko Pavlinec; Ivana Giovanna Zupičić; Dražen Oraić; Bruna Petani; Bosiljka Mustać; Željko Mihaljević; Relja Beck; Snježana Zrnčić (Environmental Monitoring and Assessment, 2020)

Neoehrlichiosis: an emerging tick-borne zoonosis caused by Candidatus Neoehrlichia mikurensis - Cornelia Silaghi; Relja Beck; José A. Oteo; Martin Pfeffer; Hein Sprong (Experimental and Applied Acarology, 2016)

Microflora and internal parasites of the digestive tract of Eurasian griffon vultures (Gyps fulvus) in Croatia - Ivna Kocijan; Estella Prukner-Radovčić; Relja Beck; Ana Galov; Albert Marinculić; Goran Sušić (European Journal of Wildlife Research, 2009)

Stichorchis subtriquetrus in European beaver from Croatia: first report - Heinz Sager; Dean Konjević; Marijan Grubešić; Zdravko Janicki; Krešimir Severin; Relja Beck (European Journal of Wildlife Research, 2005)